DEMPLOT INTEGRASI BUDIDAYA IKAN NILA, KOMBINASI PAKAN PABRIKAN DAN PAKAN ALTERNATIF LOKAL LEMNA MINOR DALAM MENCAPAI EFISIENSI PRODUKSI DI INDUSTRI RUMAH TANGGA "USAHA NILA BENAR", KECAMATAN LABUAPI, KABUPATEN LOMBOK BARAT - Awan Dermawan; Dermawan, Awan; Lestari, Dewi Putri; Mujib, Abd Saddam; Suhendri, Salwa; Adinda Titania Ratna (Jurnal Pepadu, 2025)
Nile tilapia farming at the household industry "Usaha Nila Benar", Labuapi, West Lombok, faces high production costs due to dependence on expensive commercial feed. This article discusses a community service activity aimed at improving production efficiency by integrating commercial feed with a local alternative feed from Lemna minor (duckweed). The implementation method used a participatory demonstration plot (demplot) approach. The activities included socialization, training on Lemna minor cultivation and business management, application of combined feed technology (70-80% pellets, 20-30% Lemna minor), ongoing mentoring, and evaluation. The application of feed combination successfully reduced production costs by up to 30% without sacrificing the quality and quantity of the harvest. Partners became more independent in managing their farming business by utilizing sustainable and environmentally friendly local resources. The integration of Lemna minor as an alternative feed proved effective in achieving the activity's goals: increasing production efficiency, reducing dependence on commercial feed, empowering partners, and supporting sustainable food security